2014
DOI: 10.1063/1.4904483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reactant rotational excitations on H2 + NH2 → H + NH3 reactivity

Abstract: Rotational mode specificity of the title reaction is examined using an initial state selected time-dependent wave packet method on an accurate ab initio based global potential energy surface. This penta-atomic reaction presents an ideal system to test several dynamical approximations, which might be useful for future quantum dynamics studies of polyatomic reactions, particularly with rotationally excited reactants. The first approximation involves a seven-dimensional (7D) model in which the two non-reactive N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…It is of great significance to carry out studies on the validities of the CS approximations in tetratomic and polyatomic systems, possibly combined with a full exploration of the PESs of reaction systems . To date, some efforts have been devoted to investigate the accuracy of the CS approximation in different tetraatomic and polyatomic systems . For example, the study of Lee and coworkers on the tetraatomic H 2 + D 2 reaction has first showed that the CS approximation can work well for the CID process but it cannot work well for the 4C and SE processes of this tetraatomic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of great significance to carry out studies on the validities of the CS approximations in tetratomic and polyatomic systems, possibly combined with a full exploration of the PESs of reaction systems . To date, some efforts have been devoted to investigate the accuracy of the CS approximation in different tetraatomic and polyatomic systems . For example, the study of Lee and coworkers on the tetraatomic H 2 + D 2 reaction has first showed that the CS approximation can work well for the CID process but it cannot work well for the 4C and SE processes of this tetraatomic system.…”
Section: Discussionmentioning
confidence: 99%
“…The study on the H + H 2 O reaction showed that the CS approximation is inadequate for this tetraatomic reaction especially for its abstraction channel. In the time‐dependent wave packet study of polyatomic H 2 + NH 2 reaction, the 7D CS approximation agrees satisfactorily well with the CC calculation at low collision energy range but deviates at the high collision energies. The 6D and 7D quantum dynamics study on polyatomic OH + CH 4 reaction demonstrated that the CS approximation works reasonably in computing the integral cross sections over their considered energy range.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, all vibrational modes are less effective than translational energy in promoting the reaction. Due to the high computational cost for a full-dimensional quantum study for this reaction, a seven-dimensional (7D) quantum model with two non-reactive NH bonds fixed at their equilibrium geometry was also tested 181 . It was found that the spectator-bond approximation works very well in the energy range studied, while the CS and J-shifting ICSs agree satisfactorily with the coupled-channel results in the low collision energy region, but deviate at the high energies.…”
Section: Five-atom Reactions 1 H+nh3 ↔ H2+nh2mentioning
confidence: 99%